2018
DOI: 10.11606/s1518-8787.2018052000439
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and behavior disorders among children and adolescents: a systematic review

Abstract: OBJECTIVEThis systematic review study aimed to assess the evidence available for the association between breastfeeding and behavior disorders in childhood and adolescence.METHODSThe search was carried out in the PubMed, Lilacs, and PsycINFO databases up to December 2016. Inclusion criteria were as follows: prospective, retrospective and cross-sectional studies assessing the association between breastfeeding and behavior disorders in childhood or adolescence, using psychometric tests, carried out in humans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In recent years, the mental health benefits that breastfeeding provides have garnered much more attention in neuroscientific research. Notably, breastfeeding is associated with improved cognitive development, as demonstrated by improved IQ scores [14] and a reduced risk of childhood behavioural disorders [15,16]. These findings also coincide with studies showing enhanced brain development parameters, such as white matter development in frontal and temporal regions [17] and maturation of the basal ganglia and thalamus [18].…”
Section: Introductionsupporting
confidence: 73%
“…In recent years, the mental health benefits that breastfeeding provides have garnered much more attention in neuroscientific research. Notably, breastfeeding is associated with improved cognitive development, as demonstrated by improved IQ scores [14] and a reduced risk of childhood behavioural disorders [15,16]. These findings also coincide with studies showing enhanced brain development parameters, such as white matter development in frontal and temporal regions [17] and maturation of the basal ganglia and thalamus [18].…”
Section: Introductionsupporting
confidence: 73%
“…A previous study, conducted in São Paulo [ 13 ], found the prevalence of global disability to be 62.2%, higher than that observed in the present study, although that study included individuals ≥65 years of age, rather than ≥60 years of age as in the present study. Similarly, in São Paulo and Manaus, the prevalence of global disability was higher than that reported in studies investigating younger populations [ 5 , 23 , 25 , 35 ], which is to be expected because disability is age dependent [ 12 , 20 ].…”
Section: Discussionmentioning
confidence: 95%
“…Part of the prevention effort is effective screening for chronic diseases, which are more prevalent in older adults, and controlling other conditions that can lead to disability [ 2 ]. In Brazil, three-quarters of the population over 49 years of age has at least one chronic disease [ 4 ], and 23% of the individuals in that age group already have difficulty performing at least one activity of daily living, such as dressing themselves and getting up from a chair [ 5 ]. In addition to activities of daily living, disability affects several other areas important to independent life, such as work, leisure, and participation [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in the literature that there is a relationship between breastfeeding and sleep quality in infants 24 . Also, breastfeeding is related to behavior disorders in children and adolescents 25 . However, there was no significant correlation between sleep hour and milk type in our study (Rank Biserial rrb=0.005; p=0.634) ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%